Comparison of centchroman and PPIUCD in terms of efficacy, safety and continuation rate in immediate postpartum period - Gupta, Megha; Bansiwal, Reeta; Anand, H. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Study was done to assess the efficacy, safety and continuation rate of Centchroman and IUCD administered in immediate postpartum period (within 48 hours). Methods: An interventional study was conducted in Obstetrics and Gynecology department of Safdarjung Hospital, New Delhi, at a tertiary care hospital after approval from ethical committee. 280 women were enrolled in the study and divided into 2 groups centchroman group and PPIUCD group, 140 in each group after excluding the exclusion criteria and satisfying inclusion criteria. These women were followed up at 6 week, 3 month and 6 months to study efficacy, safety and continuation rate. Results: Centchroman as contraception is safe with fewer side effects, better satisfaction rate and better continuation rate in comparison to PPIUCD. Conclusions: Centchroman is a newer contraceptive which is recently added in basket of family planning in our country to give wider choices to women. It is an indigenous product developed by central drug research institute (CDRI), Lucknow available free of cost in government hospitals. Centchroman needs more popularity and education for its widespread use.